LiDAR-Based Non-Cooperative Tumbling Spacecraft Pose Tracking by Fusing Depth Maps and Point Clouds - Gaopeng Zhao; Sixiong Xu; Yuming Bo (Sensors, 2018)
How to determine the relative pose between the chaser spacecraft and the high-speed tumbling target spacecraft at close range, which is an essential step in space proximity missions, is very challenging. This paper proposes a LiDAR-based pose tracking method by fusing depth maps and point clouds. The key point is to estimate the roll angle variation in adjacent sensor data by using the line detection and matching in depth maps. The simplification of adaptive voxelized grid point cloud based on the real-time relative position is adapted in order to satisfy the real-time requirement in the approaching process. In addition, the Iterative Closest Point algorithm is used to align the simplified sparse point cloud with the known target model point cloud in order to obtain the relative pose. Numerical experiments, which simulate the typical tumbling motion of the target and the approaching process, are performed to demonstrate the method. The experimental results show that the method has capability of estimating the real-time 6-DOF relative pose and dealing with large pose variations.